Marketing Mix Analysis of Banana Chips in the Barokah Banana Chips Household Industry, Unaaha District, Konawe Regency - Saiful Jihad; Surni; Abdi (International Journal of Technology and Education Research, 2025)
This study aims to examine the marketing mix implemented by the banana chips business "Barokah" located in Unaaha District, Konawe Regency. The research uses a descriptive quantitative method. Data were collected through questionnaires distributed to 30 respondents. The data were analyzed using the continuum line method to interpret the results. The findings indicate that the applied marketing mix falls into the "satisfied" category with a total score of 1,893 out of a maximum score of 2,400. The product dimension received the highest mean score of 4.28 and was classified as "good," indicating that consumers are satisfied with the product's quality, durability, and appearance. The price and place dimensions also fall under the good category, while the promotion dimension is in the fair category and needs improvement, particularly in the use of digital media. It is recommended that the business owner enhance promotional strategies and expand distribution channels to increase product recognition and accessibility